OzoNews Volume XX - 15 February 2020 - United Nations Environment Programme (2020)
In this issue: 1. Kigali Amendment latest ratifications 2. The OzonAction new iPIC platform - The Informal Prior informed consent system (iPIC) has been completely overhauled and updated 3. Arctic warming linked to little-studied GHGs 4. Renewed call to ban disposable cylinders 5. Japan launches Fluorocarbons Initiative, contributing to global effort to solve the climate crisis 6. Primacy of Pakistan Customs’ striking seizures and timely-interventions 7. Most industry stakeholders support HFC reduction bill 8. Fight against illegal imports of refrigerant gases into the EU 9. 12.5 tonnes of illegally imported refrigerant gases seized with OLAF’s help